Carbon Nanotubes–MnOx Nanocomposite as Support for Iron‐Based Catalysts for the Fischer–Tropsch Synthesis of Liquid Fuels. Issue 9 (13th April 2017) - Liu, Renjie; Liu, Runxue; Si, Mengyao; Lv, Jing; Ma, Xinbin; Li, Zhenhua
Abstract: A facile one‐pot hydrothermal method is developed to synthesize a series of carbon nanotubes–manganese oxide nanocomposites (CNTs–MnO x ) with different morphologies and Mn valence states. These nanocomposite materials are then utilized as catalyst supports in iron‐based Fischer–Tropsch synthesis (FTS) for the production of liquid fuels. Experimental results indicate that Fe/CNTs‐K‐190 (iron catalyst supported on the CNTs treated with KMnO4 at 190 °C) and Fe/CNTs‐KU‐190 (iron catalyst supported on the CNTs treated with KMnO4 and urea at 190 °C) display higher FTS activity than the Fe/CNTs‐K‐110 (iron catalyst supported on CNTs treated with KMnO4 at 110 °C) and Fe/CNTs‐KU‐110 (iron catalyst supported on CNTs treated with KMnO4 and urea at 110 °C). This might be due to the weak metal–support interaction and high MnO content, and the poorer stability than Fe/CNTs‐K‐110 and Fe/CNTs‐KU‐110 catalysts with nanosheet morphology might be related to the structural collapse of the nanocubes or nanorods due to MnO evolution during the FTS process. The CNTs–MnO x nanocomposite‐supported iron FTS catalysts in particular display unparalleled high C5+ selectivity (over 90 %) and very low CH4 selectivity (below 4.6 %). The unique CNTs–MnO x nanocomposites may open a new window for the understanding, design, synthesis, and optimization of iron catalysts toward high‐efficiency transport fuel production. Abstract : Thanks for the support ! The facile one‐pot synthesis of CNTs–MnO x nanocomposites is reported as a promising iron‐based Fischer–Tropsch catalyst supports to produce liquid fuel. The unique CNTs–MnO x nanocomposites may open a new window for the understanding, design, synthesis, and optimization of iron catalysts toward high‐efficiency transport fuel production.